Relating the Slovenian secondary school English language national examinations to the CEFR - Ilc, Gašper (Linguistica (Ljubljana), 2014)
The present paper draws on the report of a five-year project that aligned the Slovenian national exams in English to the Common European Framework of Reference for Languages: Learning, teaching, assessment (CEFR). Discussed here are the key findings of the relating project, carried out by the National Examination Centre, a central institution for external assessment in Slovenia, for the following exams: the Vocational Matura (for technical secondary schools, vocational-technical schools, and vocational courses) and the General Matura (for general secondary education programmes). The focus of the paper is on the interpretation of the findings of the project, the significance of relating the aforementioned exams to the CEFR, the implications of project results for future language test development and, most importantly, the impact of the findings on the development of secondary school-level English education programmes in Slovenia.
Keywords: anglais; angleščina; baccalauréat; Cadre européen commun de référence pour les langues; CECRL; English; matura; nacionalni izpiti; preverjanje; programmes d'études secondaires; SEJO; Skupni evropski jezikovni okvir; tuji jeziki; učni načrti; vérification